Pulmonary Atresia with Intact Ventricular Septum associated with Ventriculo-Coronary Arterial Communication in a Fetus at 21 Weeks of Gestation - Can Yilmaz Yozgat; Yanki Celik Yilmazer; Yilmaz Yozgat (Case Reports in Obstetrics and Gynecology)
Pulmonary atresia with the intact ventricular septum (PA-IVS) is a rare anomaly that has an absent communication between the right ventricle and pulmonary arterial circulation. PA-IVS has a hypoplastic and hypokinetic and thickened right ventricle with the intact ventricular septum. It can be diagnosed with PA-IVS in routine obstetric ultrasound examination because the four-chamber view of PA-IVS is generally abnormal. The size of the right ventricular cavity is proportional to the Z value of the diameter of the tricuspid valve. The essential associated cardiac finding of PA-IVS is ventricular-coronary arterial communications (VCAC). The hypertensive RV forces blood through the intramyocardial sinusoids with continuous fistulous contact with the epicardial branches of RCA. It is called the VCAC. A color Doppler can detect VCAC due to its location in the pericardium along the coronary artery. If patients have VCAC and tricuspid Z score below -4, all of these conditions are infallible signs of high mortality rates in their fetal or postnatal lives. Our aim in presenting this case is to remind perinatologists if they detect an abnormal four-chamber view of the fetus’s heart, they should also carefully examine whether VCAC exists. Herein, we report a case of PA-IVS and VCAC at 21 weeks’ gestation with fetal echocardiographic images.